Pengkajian Kebiasaan Konsumen Muslim Terhadap Niat Menggunakan Produk Perbankan Syariah di Kabupaten Bogor - Abdul Aziz (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyse customer behaviour in saving in Islamic banking using the Theory of Planned Behavior (TPB) framework which is extended with religiosity variables to increase the external validity of the model and understand consumer behaviour more comprehensively. The method used is quantitative research with causality analysis through the Structural Equation Modeling (SEM) approach using LISREL software version 8.70, based on data from 180 respondents. The results showed that people's positive attitudes, subjective norms, and perceived behavioural control significantly influenced the intention to use Islamic banking products, with subjective norms as the most dominant variable. In addition, perceived convenience and ability also affect both intention and actual behaviour, while religiosity only has an impact on intention with no significant effect on actual behaviour. These findings indicate a gap between religious beliefs and actual actions in the use of Islamic banking products.